Student-athletes 'self confidence level during MASUM competition - Vincent A. Parnabas; Yahaya Mahamood; Julinamary Parnabas (Pusat Perkembangan Pelajar ,U.K.M, 2013)
Self-confidence is an athlete 's beliefthat he or she can successfully execute and carry out an appropriate performance. Many researches indicated that high level of self confidence among elite athletes enhance performance. In many research reviews, researchers have found that low level of self confidence had deteriorating effect on athletes 'or teams performance. Elite athletes are well-known for high self confidence levels. However, to date there has been no attempt to examine self confidence level among athletes of nori--elite. Most of the previous researches focus on elite athletes, while ignoring less successful athletes. Therefore, the main aim of the study was to describe and compare the self-confidence level differences among different categories of skills of athletes. The present study also compared the level of self confidence among gender. Data was collected from 205 student-athletes, using a 27 item Competitive State Anxiety Inventory-2, during MASUM (Sport between Universities) competition. The results showed that national level athletes obtained the highest score on self-confidence. Furthermore, university and district level athletes exhibit the lowest level of self-confidence. The result also showed that male student- athletes obtained higher score on self confidence compared females. Based on the current results, it is recommended that sport psychologists, sport counselors and coaches in Malaysia use the findings to design appropriate training programs to help district, university level and female athletes to acquire higher level of self confidence to enhance their performance in sports.